Design of an Emergency 3D Printed Electro-Mechanical Ventilator with Bag-Valve–Mask (BVM) - Lakshmi Sramika, M.; Rajesh, J. (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
As a result of the COVID-19 epidemic, there are severe shortages of ventilators caused all across the world. To overcome this problem a 3D printed manual ventilator is a simple type of ventilator that is manually operated and relies on a bag and mask to open the airway and provide enough ventilation. (Bag-Valve-Mask) is an important aspect of manual ventilation since it enhances airflow as well as respiration these bags are return to their original shape spontaneously after being compressed. In this work a simplified mechanism of a 3D printed mechanical ventilator with a BVM is proposed and designed for ventilation. The BVM is operated by a battery and a DC motor driven by a 3D printed rack and pinion mechanism. The rack and pinion mechanism compress and decompress the bag in response to signal. The main advantage of this project is it can be sent to hospitals in rural areas for quick treatment at a low cost and with minimal risk. It can be operated by anyone because it does not require the study or training of ventilation rules like an ICU ventilator. The proposed system is risk-free, safe, and repairable. The accuracy of the angle, volume, and respiratory measurements were absolutely close to traditional one. This portable ventilator equipment can be used in rural or general hospitals, as well as ambulances, to provide rapid care.